Fostering Inclusion of Disabled Youth through Young Adult Literature: Action Research with Wonder - Judith A. Hayn; Karina R. Clemmons; Heather A. Olvey (University of Oklahoma Libraries, 2016)
It is imperative that we insist that meaningful inclusion of students with disabilities is an issue upon which schools, administrators, and teachers must continue to improve. The authors believe that secondary classrooms are excellent platforms to discuss issues of disability in an attempt to bridge students to the place of empathy and understanding. This study shows that exposing preservice teachers to literature about people with disabilities has the potential to transform their practice.